2009
DOI: 10.1523/jneurosci.1246-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Newborn Auditory Cortex to the Temporal Structure of Sounds

Abstract: Understanding the rapidly developing building blocks of speech perception in infancy requires a close look at the auditory prerequisites for speech sound processing. Pioneering studies have demonstrated that hemispheric specializations for language processing are already present in early infancy. However, whether these computational asymmetries can be considered a function of linguistic attributes or a consequence of basic temporal signal properties is under debate. Several studies in adults link hemispheric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
205
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(242 citation statements)
references
References 50 publications
27
205
3
2
Order By: Relevance
“…Several studies have linked hemispheric specialization for speech to an asymmetry in cortical auditory tuning and revealed that the auditory cortices are differentially sensitive to particular spectrotemporal features: slow acoustic amplitude modulations (3-7 Hz AM) and spectral aspects, like pitch, are preferentially processed in the right auditory cortex, whereas temporal aspects, like duration, rhythm and faster modulations (12-50 Hz AM), are more left lateralized (e.g., Boemio et al 2005;Jamison et al 2006;Poeppel 2003;Rosen et al 2011;Schönwiesner et al 2005;Zatorre and Belin 2001;Zatorre and Gandour 2008). Given that speech perception requires an accurate tracking of fast temporal cues, e.g., formant transitions (Schwartz and Tallal 1980), it seems natural that speech perception, and by extension linguistic processing, is lateralized to the left hemisphere (Telkemeyer et al 2009; but see Abrams et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked hemispheric specialization for speech to an asymmetry in cortical auditory tuning and revealed that the auditory cortices are differentially sensitive to particular spectrotemporal features: slow acoustic amplitude modulations (3-7 Hz AM) and spectral aspects, like pitch, are preferentially processed in the right auditory cortex, whereas temporal aspects, like duration, rhythm and faster modulations (12-50 Hz AM), are more left lateralized (e.g., Boemio et al 2005;Jamison et al 2006;Poeppel 2003;Rosen et al 2011;Schönwiesner et al 2005;Zatorre and Belin 2001;Zatorre and Gandour 2008). Given that speech perception requires an accurate tracking of fast temporal cues, e.g., formant transitions (Schwartz and Tallal 1980), it seems natural that speech perception, and by extension linguistic processing, is lateralized to the left hemisphere (Telkemeyer et al 2009; but see Abrams et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These connections were, by contrast, absent in the novel-word group. This pattern indicates a fundamental role of the RT region [known to process the slow information associated with speech prosody (28,47) and the prosodic information carried by vowels in single words (11)] as a hub modulating the recognition response. Altogether, this pattern reflects a precocious functional specialization of a network including the temporal to the parietal and frontal connections in the right hemisphere [associated with retrieval in adults (37,(48)(49)(50)(51)] supporting the recognition of particular features of word sounds at birth.…”
Section: Discussionmentioning
confidence: 93%
“…Each of these areas appears to support relatively specialized functions in newborns. Temporal areas are mainly involved in perception of the speech signal, with those in the left hemisphere dedicated to the processing of fast phonemic transitions and those in the right one to the processing of the slow acoustic modulations associated with prosody (28). Frontal and parietal regions are believed to sustain important domain-general functions from early infancy (29).…”
Section: Significancementioning
confidence: 99%
“…with different temporal structures [21][22][23] , and the relation of hemodynamic responses among the cortical regions 24 . The results of this group were consistent as they reported that the right and left auditory cortex are equally sensitive to rapid acoustic modulations, while the slow ones are preferably processed by the right auditory cortex 21,22 .…”
Section: Figura 2 Principais Características Dos Artigos Selecionadomentioning
confidence: 99%